UNRAVELLING THE MASTER’S NARRATIVE, WRITING BIOMYTHOGRAPHY IN ZAMI - DEY, NIRUPAMA (International Journal of Psychosocial Rehabilitation, 2020)
Audre Lorde’s Zami (1982/1993) has occupied a unique place in Black literature as an autobiographical work, discussing lesbian relationship among women of different races, by a black lesbian writer. Her autobiography is a biomythography, which subverts the concept of life-writing as a genre using only facts and posits the necessity of life-writing to be done with an awareness of the power relations within which human social identity is situated. To this end, Lorde employs many strategies, namely examining the race, gender, sexuality as a nexus within which her identity is situated, rewriting demeaning myths and stereotypes of black lesbians, breaking the linear narrative pattern to re-script the black lesbian ‘I’ and inscribing black lesbian self in actual spaces (the ‘lesbian bar culture’) and discursive spaces (the print culture) where it is silenced. In Lorde’s hands, life writing is radically re-envisioned. She transforms autobiography from a writing of identity to a writing of self with the objective of imagining change.